Shared values through human resource management: In supporting the transformation plan - Hasnan, Norlena; Razalli, Mohd Rizal; Mohd Sharif, Kamal Imran (2015)
Malaysia needs to work fast and smart in order to realize the achievement of Vision 2020.The Government recognised that the departments underperform largely due to the status quo, i.e. the limitations of the way the Government was structured and organised.Thus in order to bring about the transformation, shared values must be embedded in the organization culture. Values refer to the standards and expectations hold by the employees of the organization that guide aspects of practice performance.Generally, in services, the core values that support, respect choice, collaboration, and customer service are critical foundation stones of a trusting therapeutic relationship.Hence, this case is related to one of the government department who put great effort to transform.Before the department can move forward for the transformation agenda, it is critical to understand their current values and practices, which subsequently enable to identify the performance gap that hindered the achievement of the assigned target. The case provides valuable insight on the necessary part of the transformation process, particularly in developing the right values and practices in the government sectors.